(untitled) (Годишен зборник на Филозофски факултет - Скопје, 2023)
In this text an overview is offered of some of the most significant categories of the demonic from the Mesopotamian beliefs – of hybridity and liminality – through some examples of the conceptions of the demons Pazuzu and Lamaštu. Firstly, the logicaldialectical relations of the sphere of the demonic as external and foreign, opposed to the homely, familiar and close sphere are sketched; as well as the relation of the demonic as terrifying and potentially menacing, as opposed to the ordered civilized sphere with norms of conduct. Then, several representations of the concepts of Pazuzu as an ambivalent demon are listed – he is an evil fighting against evil, his nemesis, Lamaštu, and precisely because of the need for him to be efficient in his protective function, he has to be a horrifying, dangerous demon. This is shown through the descriptions of the available incantations and preserved rituals. The terrifying threat of Lamaštu against the most precious part of the communities – the new generations - through her snatching and destroying of the newborns, is shown through the representations of her hybridity and monstrosity, and mainly through the incantations for her removal and (permanent) expulsion.